Environmentally Benign Syntheses of α-Substituted Phosphonates: Preparation of α-Amino- and α-Hydroxyphosphonates in Water, in Ionic Liquids, and under Solvent-Free Conditions - Olszewski, Tomasz K. (Synthesis, 2014)
Due to the interest in α-amino- and α-hydroxyphosphonates and their derivatives, which arises from the important biological activity exhibited by those compounds, the development of efficient protocols for their preparation is of great importance. In the last 10 years however, the chemistry of α-amino and α-hydroxyphosphonates has been witness to an explosion of research activities in the field of application of environmentally benign media. This fact can be partially attributed to the development of the field of green and sustainable chemistry and especially the implementation of green solvents that has a large potential to contribute to more sustainable processes in chemical, pharmaceutical and processing industries. This review provides the reader with an in-depth overview of advances in the synthesis of α-amino- and α-hydroxyphosphonates under eco-friendy conditions compiled into sections with respect to product type and reaction medium.1 Introduction2 Syntheses of α-Aminophosphonates in Environmentally Friendly Media2.1 Reactions in Water2.2 Reactions in Ionic Liquids2.3 Solvent-Free Protocols2.3.1 Reactions without Any Additives2.3.2 Reactions Promoted by Ultrasound or Microwave Irradiation2.3.3 Catalyzed Reactions under Solvent-Free Conditions3 Preparation of α-Hydroxyphosphonates under Environmentally Friendly Conditions 3.1 Reactions in Water3.2 Reactions under Solvent-Free Conditions 4 Concluding Remarks
Keywords: phosphorylation; Schiff bases; ionic liquids; imines; green chemistry; phosphonic acid diesters; trialkyl phosphite